Growth and characterization of a new NLO material: 4-methoxy benzoin - Thanuja, B.; Nithya, G. Nithya; Kanagam, C. (Photonics Letters of Poland, 2012)
Single crystals of 4-methoxy benzoin (4MB), an organic nonlinear optical material have been synthesized by a slow evaporation technique at room temperature. The crystalline nature was confirmed by single crystal X-ray diffraction analysis. The chemical composition of grown crystals was determined by FTIR spectra. Optical absorption studies have shown that UV cut off wavelength of the grown crystal is at 400nm and it has wide transparency window. The second harmonic generation (SHG) efficiency of the grown crystal was confirmed by the Kurtz and Perry powder technique. Full Text: PDF References D.S. Chemla, J.Zyss, Nonlinear optical properties of organic molecules and crystals (Academic Press 1987) H. Ringertz,"The molecular and crystal structure of hippuric acid", Acta Crystallogr. B 27, 285 (1971)[CrossRef] T. Pal, T. Karand, B. Gabriel, L. Rigi,"Morphology, Crystal Structure, and Thermal and Spectral Studies of Semiorganic Nonlinear Optical Crystal LAHClBr", Cryst. Growth Des. 4, 43 (2004)[CrossRef] Setsuo Kashino and Masao Haisa,"Structure of p-anisoin, C16H16O4", Acta cryst. C41, 1066-1069(1985)[CrossRef] S.K. Kurtz, T.T. Perry,"A Powder Technique for the Evaluation of Nonlinear Optical Materials", J. Appl. Phys. 39, 3798 (1968)[CrossRef]